2019
DOI: 10.3390/v11010075
|View full text |Cite
|
Sign up to set email alerts
|

Co-Delivery Effect of CD24 on the Immunogenicity and Lethal Challenge Protection of a DNA Vector Expressing Nucleocapsid Protein of Crimean Congo Hemorrhagic Fever Virus

Abstract: Crimean Congo hemorrhagic fever virus (CCHFV) is the causative agent of a globally-spread tick-borne zoonotic infection, with an eminent risk of fatal human disease. The imminent public health threat posed by the disseminated virus activity and lack of an approved therapeutic make CCHFV an urgent target for vaccine development. We described the construction of a DNA vector expressing a nucleocapsid protein (N) of CCHFV (pV-N13), and investigated its potential to stimulate the cytokine and total/specific antibo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…Five microliters of template RNA (500 ng) was added to complete the master mix to 20 μl. The cycling conditions were as follows: cDNA synthesis at 50 °C for 10 min, initial denaturation at 95 °C for 2 min, and 40 cycles of denaturation at 95 °C for 5 s, and annealing/extension at 60 °C for 30 s. The primers and probe were targeting the nucleoprotein gene (small segment) as previously described [ 27 ]: qPCR-F (5′-GGACATAGGTTTCCGTGTCA-3′), qPCR-R (5′-TCCTTCTAATCATGTCTGACAGC-3′) and qPCR-probe (5′-FAM-AGAACAACTTGCCAATTACCAACAGGC-BHQ1-3′). Standard linear plasmids were prepared by 10-fold dilutions equivalent to 2 × 10 3 to 2 × 10 8 copies/reaction mixture using pCD-N1 as the template [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five microliters of template RNA (500 ng) was added to complete the master mix to 20 μl. The cycling conditions were as follows: cDNA synthesis at 50 °C for 10 min, initial denaturation at 95 °C for 2 min, and 40 cycles of denaturation at 95 °C for 5 s, and annealing/extension at 60 °C for 30 s. The primers and probe were targeting the nucleoprotein gene (small segment) as previously described [ 27 ]: qPCR-F (5′-GGACATAGGTTTCCGTGTCA-3′), qPCR-R (5′-TCCTTCTAATCATGTCTGACAGC-3′) and qPCR-probe (5′-FAM-AGAACAACTTGCCAATTACCAACAGGC-BHQ1-3′). Standard linear plasmids were prepared by 10-fold dilutions equivalent to 2 × 10 3 to 2 × 10 8 copies/reaction mixture using pCD-N1 as the template [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…To investigate viral load and replication pattern in the different human and bovine kidney cell lines, a local CCHFV strain Ank-2 (GenBank Accession number: MK309333) [27] was used in the study. CCHFV strain Ank-2 was isolated in SW-13 cells and after two rounds of virus propagation, virus replication was verified by real-time PCR targeting the S segment and follow-up sequencing.…”
Section: Virus and Analysis Of Growth Kinetics In The Cell Linesmentioning
confidence: 99%
“…To confirm the in vitro expression of N proteins from the pCD-N1 and pDC516-N constructs, an indirect immunofluorescence assay (IIFA) was performed in BHK21-C13 cells, as previously described [23]. Briefly, BHK21-C13 cells were cultivated in 24-well plates for 24 h before pCD-N1 transfection by Lipofectamine3000.…”
Section: Methodsmentioning
confidence: 99%
“…The CCHFV Ank-2 strain, which was previously demonstrated to be lethal for IFNα/β/γR−/− mice, was used in the intra-peritoneal challenge experiment [23]. The immunization schedule (vaccine constructs and their respective backbones) of IFNα/β/γR−/− mice (8–12-week-old female) was similar to BALB/c mice.…”
Section: Methodsmentioning
confidence: 99%
“…Although the glycoproteins of CCHFV exhibit the greatest genetic diversity, we detected sustained CCHFV-specific T-cell responses against the more-conserved CCHFV nucleoprotein. Vaccine-induced responses solely against the nucleoprotein can be protective (24,25), and it is therefore likely that immune responses against the more-conserved CCHFV nucleoprotein could provide cross protection. Studies with monoclonal antibodies against the glycoproteins have shown that although there exist antigenic differences among diverse strains of CCHFV, there are neutralizing epitopes conserved among divergent strains (26,27).…”
Section: Figmentioning
confidence: 99%